Effects of high pressure on cell membrane permeability and activity of amylase of rice seeds - YAN Pu; Li Gui-shuang; DUAN Jun (浙江大学学报. 农业与生命科学版)
Using the rice seed of Qiu Guang as material, the effects of high pressure on cell membrane permeability and activity of amylase were studied after treating with different pressure on rice seeds with different soaking time, and the relationships between germination power, germination rate and relative conductivity, activity of amylase were analyzed. The results showed that, both germination power and germination rate decreased with pressure increasing, while the cell membrane permeability of seeds increased with pressure increasing, and there were significant differences among the different soaking time; the activity of α-amylase and β-amylase of germinating seeds decreased significantly after treated with high pressure; there was a negative correlation between germination power, germination rate and the increase percentage of relative conductivity, while the correlation was positive obviously between germination power, germination rate and the activity of amylase. The above results indicated that there were relationships among the decrease of germination power and germination rate and the increase of relative conductivity, the decrease of activity of amylase after treated with high pressure.